2006
DOI: 10.1007/s00244-004-0233-7
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Australian Sediment Quality Guidelines

Abstract: Interim sediment quality guidelines (ISQGs) adapted recently to Australia from North American effects-based guidelines were evaluated with matching chemical and toxicological data collected for sediments (n = 103) from Sydney Harbour and south coast estuaries of New South Wales. The incidence of toxicity for the test battery was low (7%) among samples with all chemical concentrations below ISQG-Low values, indicating these guidelines are accurate and protective of non-toxic conditions. The incidence of toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The estuary catchment (480 km 2 ) is highly urbanised (78%) and was once an important industrial hub. Bottom sediment in many parts of the estuary contain high levels of organic McCready et al, 2000McCready et al, , 2006a and inorganic contaminants (Birch and Taylor, 1999) presently sourced mainly from stormwater (Birch and McCready, 2009;Birch et al, 2013).…”
Section: Study Areamentioning
confidence: 99%
“…The estuary catchment (480 km 2 ) is highly urbanised (78%) and was once an important industrial hub. Bottom sediment in many parts of the estuary contain high levels of organic McCready et al, 2000McCready et al, , 2006a and inorganic contaminants (Birch and Taylor, 1999) presently sourced mainly from stormwater (Birch and McCready, 2009;Birch et al, 2013).…”
Section: Study Areamentioning
confidence: 99%
“…Marine sediment quality is used as a general measure of marine contamination in China (Zhang et al 2007). Canada, Australia, and New Zealand have also their own SQG (Thompson et al 2005;McCready et al 2006;Abrahim et al 2007). …”
Section: Introductionmentioning
confidence: 98%
“…When the median 5% effect values (HC 5;50 ) and their lower 95% confidence limits (HC 5;95 ) (Table 5) are compared with the Australian ISQG values (Table 1) the derived values for Cd fall between the High and Low guidelines but the values for Cu and Zn are substantially lower (up to a factor of 28 comparing the HC 5;95 with the ISQG-Low for Cu). The current interim guidelines were evaluated for Sydney Harbour using matched chemical and toxicological data by McCready et al (2006b) and found to be reasonable. Similarly, the derived HC values (Table 5) also need to be considered against estimated background sediment metal concentrations in Sydney Harbour.…”
Section: Comparisons With Other Resultsmentioning
confidence: 99%